Reduction of the Authority Inequality between the Community Board with the Member of Local Government Council - Kunnu, Wittawat (Hatyai Academic Journal, 2023)
The inequality is a challenging task of most local administrative organization. The factor leads to the study of the reduction of inequality in roles and duties of committees and local administrative organization council members. The purposes of this study are as follows 1) to study about which factors can read to the reduction of inequality in roles and duties of community committee of local government council members, and 2) to study the guidelines for reducing inequality in roles and duties of community committees and local government council members towards the administration of local government organizations. This study is a qualitative research. The data is collected from 22 key informants. The key informants are selected by purposive sampling and snowball sampling. The data instruments are in-depth interview and semi-structured interview. The findings indicated that factors affecting the reduction of power inequality are the legal side. It is found that the hierarchy of the law governing the role of the municipal council member was higher than the law or regulation that recognized the position of the community committee. In terms of morale, the community chairmen and the community committee are not paid for their work. Therefore, the approaches to reduce the inequality of authority are the establishment of laws and regulations to support the positions of community committee and community chair. The law should be pushed into the draft regulations of the Ministry of Interior on Community Committees and Municipalities. It can lead to a practical enforcement so that the laws and regulations that support the positions. Providing compensation to community committees in the form of monthly remuneration or meeting allowance should be imposed.